COMPARING SOME IDIOMATIC EXPRESSIONS BETWEEN ENGLISH AND UZBEK LANGUAGES WITH THE HELP OF JANE AUSTENʼS BOOK “PRIDE AND PREJUDICE”. (Journal of Universal Science Research, 2023)
This article aims to compare, to analyse and to find idomatic phrases, metaphors and idioms in “Pride and prejudice” book. Pride and Prejudice is a novel that frequently used idioms with metaphors. For instance, Mary says that they must "stem the tide of malice" (p. 245). The reader understands that Mary is not referring to a literal ocean tide. She is using the word metaphorically. In addition to, it helps to identify what do these idioms mean and how many are there? According to meanings of them they were used coherently in this work, and one by one we will know about their meanings. These idomatic phrases, metaphors and idioms serve to describe all scenes of work naturally, and they help to understand and to be a page turner. However, when we translate them other languages without knowing the meaning of idioms fully it reacts to readers differently, so while translating we must comb their meanings again and again. It’s known that while we are using idomatic phrases or metaphors there are some similarities and differences between Uzbek and English languages. According to the contexts we mostly use proper idioms when we compose works such as novel.